Implementación en DSPIC de un algoritmo óptimo para la estimación de velocidad de giro (2014)
In  this  paper  we  present  the  implementation  of  a  new  method  to  measure  angular  speed  when the  data  come  from  an  incremental  encoder.  Part  of the method is implemented in a dsPIC, whereas the remaining  part  was programmed  in  Simulink.  The  main advantage  of  the  new  method  consists  of  having  just one approximation at constant speed, whereas traditional  methods  oscillate  between  two  values.  The  speed  control  of  a  motor  serves  as  an  application  of  the  new  method,  which  allows  concluding  that  the  proposed  method can be used to estimate the rate of change of a variable even when the data do not come from an incremental encoder.